2003
DOI: 10.1177/104063870301500504
|View full text |Cite
|
Sign up to set email alerts
|

Severe Persistent Orf in Young Goats

Abstract: Abstract. Orf (contagious ecthyma) is a viral disease of small and wild ruminants, humans, and less frequently other species. In sheep and goats, the disease is characterized by the formation of vesiculo-proliferative lesions in the skin of lips and nostril. Here, a form of generalized orf in 16 goat kids from 2 different locations in west Texas is described. The disease was characterized by multifocal, severe, proliferative dermatitis that persisted from about 2 months of age until the goat kids were euthaniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 22 publications
3
48
0
3
Order By: Relevance
“…Boer goats and crosses are more susceptible to ORFV infection and develop severe disease according to existing reports [24]. In this study, Anglo-Nubian goats were more susceptible to orf, whereas Saanen dairy goats appeared to be more resistant to ORFV infection.…”
Section: Discussionsupporting
confidence: 55%
“…Boer goats and crosses are more susceptible to ORFV infection and develop severe disease according to existing reports [24]. In this study, Anglo-Nubian goats were more susceptible to orf, whereas Saanen dairy goats appeared to be more resistant to ORFV infection.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have shown that aged sheep and goats remained susceptible to Orf virus infection if they had not undergone a previous attack of the disease during their early life (Ismail, 1994 (De La Concha-Bermejillo et al, 2003;Yeruham et al, 2000). In addition, the severity of the disease can be intensified by exposure of animals to stress and immunosuppression conditions as a result of therapy or primary viral infection (Hosamani et al, 2009).…”
Section: Clinical Managementmentioning
confidence: 99%
“…In more severe cases, the skin of the eyes and feet also may be affected (Allworth et al, 1987;McKeever et al, 1988). Persistent infections with severe, generalized skin proliferative lesions have been reported; (De La Concha-Bermejillo et al, 2003). Persistently infected carrier goats and sheep have been demonstrated to be the main source of disease and infection in the farm that can relapse during time of stress (Nettleton et al, 1996).…”
Section: Ontagious Ecthymamentioning
confidence: 99%
See 1 more Smart Citation
“…CE is a self-limiting disease, and spontaneous recovery without treatment occurs within 3-4 weeks in susceptible species. However, the recovery period for CE can be affected by some variables, including nutritional and passive transfer status, season type, and the presence of a secondary bacterial infection, such as staphylococci, alpha haemolytic streptococci or Corynebacterium (2,15). These variables may increase the mortality rate of the affected animals (13).…”
Section: Resultsmentioning
confidence: 99%